Adsorption deformation of microporous composites. Issue 10 (24th November 2015) - Coudert, François-Xavier; Fuchs, Alain H.; Neimark, Alexander V.
Abstract : We demonstrate a theoretical model to describe the behavior of flexible adsorbent materials, or soft porous crystals, when used in practical applications as nanostructured composites such as core–shell particles or mixed matrix membranes. Abstract : We study here the behavior of flexible adsorbent materials, or soft porous crystals, when used in practical applications as nanostructured composites such as core–shell particles or mixed matrix membranes. Based on simple models and the well-established laws of elasticity, we demonstrate how the presence of a binder results in an attenuation of the adsorption-induced stress and deformation. In the case where the adsorbent undergoes adsorption-induced structural transitions, such as the gate opening phenomenon occurring in some metal–organic frameworks, we show that the presence of the binder will result in shifts of the adsorption-induced transition pressures.